Self Esteem dengan Kecenderungan Self Injury pada Mahasiswa yang Mengalami Putus Cinta: Arigi Ade Purwandra, Yuarini Wahyu Pertiwi, Farida Novitasari - Ade Purwandra, Arigi; Wahyu Pertiwi, Yuarini; Novitasari, Farida (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
It is commonly happened in dynamic love relationship to breakup each other, in which so that they do actions that can hurt themselves, this is done by someone to deal with emotional pain, self-emptiness, loneliness, loss. , and satisfy the desire to punish oneself by causing injuries to the body, this is called self-injury. Self-injury is a form of behavior carried out by individuals to deal with emotional pain, this behavior is carried out very intentionally but the individual does not intend to commit suicide. One that affects self-injury is self-esteem. Self-esteem is the result of an individual's evaluation of himself which is expressed in his own attitude. This study aims to determine whether there is a relationship between self-esteem and self-injury in Bhayangkara University, Jakarta Raya students who experience a breakup. The subjects used in this study were students of Bhayangkara University, Greater Jakarta with a total of 100 subjects. The results of the non-parametric correlation test of Spearman's Rho showed a relationship of -0.403** with a significance of 0.000 (p < 0.001). The results show that there is a relationship with a significant negative correlation between self-esteem and self-injury in Bhayangkara University, Jakarta Raya students who experience a breakup. That is, the higher self-esteem in students, the lower students do self-injury, and vice versa